Ternary Transition Metal Chalcogenide Nb2Pd3Se8: A New Candidate of 1D Van der Waals Materials for Field-Effect Transistors - Jeong, Byung Joo; Choi, Kyung Hwan; Jeon, Jiho; Yoon, Sang Ok; Chung, You Kyoung; Sung, Dongchul; Chae, Sudong; Kim, Bum Jun; Oh, Seungbae; Lee, Sang Hoon; Woo, Chaeheon; Kim, Tae Yeong; et al. (Advanced Functional Materials, 2022)
In this work, high-quality 1D van der Waals (vdW) Nb2Pd3Se8 is synthesized, showing an excellent scalability from bulk to single-ribbon due to weakly bonded repeating unit ribbons. The calculation of electronic band structures confirmed that this novel Nb2Pd3Se8 is a semiconducting material, displaying indirect-to-direct bandgap transition with decreasing the number of unit-ribbons from bulk to single. Field effect transistors (FETs) fabricated on the mechanically exfoliated Nb2Pd3Se8 nanowires exhibit n-type transport characteristics at room temperature, resulting in the values for the electron mobility and Ion/Ioff ratio of 31 cm2 V−1 s−1 and ≈104, respectively. Through transport measurements at various temperatures from room temperature down to 90 K, it is confirmed that Nb2Pd3Se8 FETs can achieve negligible Schottky barrier height (SBH) for the Au contacts at the temperature range, displaying clear ohmic contact characteristics. Furthermore, top-gated FETs fabricated with the Al2O3 dielectric layer are studied simultaneously with back-gated FETs.
Keywords: 1d van der waal material; Field-effect transistor; High quality; N-type behavior; Repeating unit; Schottky-barrier heights; Synthesised; Transition metal chalcogenides; Transition-metal chalcogenides; Van der Waal